Scaphoid Fracture: Functional Outcome Following Fixation with Herbert Screw - Parajuli, N P; Shrestha, D; Dhoju, D; Shrestha, R; Sharma, V (Kathmandu University Medical Journal, 2012)
Background Most scaphoid fractures though heal uneventfully with cast treatment, immobilization with cast is associated with complication like wrist stiffness. Open reduction and fixation with Herbert Screw though technically demanding procedure can yield excellent results and prevents complication like nonunions and loss of wrist function. Objectives To assess clinical outcome and radiological union of scaphoid fracture after operative management following Herbert screw fixation in patient attending Dhulikhel Hospital. Methods All scaphoid fracture, treated from Feb 2007 till Feb 2011, were retrospectively studied in Dhulikhel Hospital, Kathmandu University Hospital. Fifteen patients with scaphoid fractures were treated with Herbert screw. Fourteen were males and one was female. Serial radiographs were taken to assess radiographic union and functional outcome was assessed using Modified Mayo wrist score. Results Out of 15 patients, 13 scaphoid had waist fractures and two had proximal pole factures. All scaphoid were treated with open reduction and Herbert screw fixation either by volar approach or by dorsal approach. All fractures maintained good alignment post operatively. Nine (60%) patients had excellent results with normal wrist range of motion, five (33.3%) patients had good results and one (6.7%) patient had poor outcome. In 14 (93.3%) patients good radiological union was seen at final follow up at six months time. Conclusion Fixation with Herbert screw for scaphoid fracture is an effective and convenient way of treatment with satisfactory functional outcome and less complication. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6342 Kathmandu Univ Med J 2011;9(4):267-73